Review of the CFRAMP Project : progress and achievements of the CFRAMP Project and some perspectives for the future in fisheries management for CARICOM/CARIFORUM countries under a common Caribbean fisheries mechanism - Caddy, John F. (CARICOM Fisheries Unit Belize CityBZ, 2001)
Evaluates the CFRAMP Project and focuses on some future perspectives for future management of marine resources under the Caribbean Regional Fisheries Mechanism.